2009
DOI: 10.1088/0022-3727/42/16/165303
|View full text |Cite
|
Sign up to set email alerts
|

Formation and characterization of ZnO : Tm+optical waveguides fabricated by Tm+and O+ion implantation

Abstract: Planar optical waveguides were formed in ZnO crystal by Tm+ and O+ ion implantation. The distributions of Tm+ in as-implanted and annealed ZnO samples were investigated by the RBS technique. A shift of the Tm+ peak towards the sample surface and out diffusion were observed after thermal treatment and subsequent O+ ion implantation. Waveguide formation was determined after O+ implantation in Tm+-implanted ZnO crystal. By using the prism-coupling method two guided modes were detected. The refractive index profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…It can be found that the experimental depth of damage peak is in good agreement with the theoretical predication, which is located at around 0.85μm below sample surface. The FWHM of practical damage profile is broader than that of simulation result, it is normal and can be found in other reports [13] Implantation with three different He + -ion doses doesn't result in dramatic lattice damage. The highest damage ratio of sample 1 is lower than 10%, even for the implantation at dose of as high as 4×10 16 ions/cm 2 , the induced peak damage ratio is only about 15%.…”
Section: A Lattice Damage In As-implanted Samplessupporting
confidence: 74%
“…It can be found that the experimental depth of damage peak is in good agreement with the theoretical predication, which is located at around 0.85μm below sample surface. The FWHM of practical damage profile is broader than that of simulation result, it is normal and can be found in other reports [13] Implantation with three different He + -ion doses doesn't result in dramatic lattice damage. The highest damage ratio of sample 1 is lower than 10%, even for the implantation at dose of as high as 4×10 16 ions/cm 2 , the induced peak damage ratio is only about 15%.…”
Section: A Lattice Damage In As-implanted Samplessupporting
confidence: 74%
“…Zinc oxide has attracted extensive interest because of its important role in various applications, for example, gas sensor [2], surface acoustic wave devices [3], optical waveguides [4] as well as blue/UV light emitting devices [5]. Compared to other kinds of nanostructured lms, the ZnO lms have the advantages of structural versatility, easy fabrication and availability, which make them ideal templates for nanostructure construction [6,7].…”
Section: Introductionmentioning
confidence: 99%